ENVIRONMENTL FACTORS AFFECTING SOME REPRODUCTIVE TRAITS IN NILI RAVI BUFFALOES - A. Ali; K. Javed; N. Ahmad; S. U. Rehman (Journal of Animal and Plant Sciences, 2011)
Data on 451 records for service period and 405 records for services per conception of Nili-Ravi buffaloes maintained at Livestock Experiment Station, Bahadurnagar, Okara spanned over a period from 1997 to 2006 were analyzed to examine the effect of year, season of calving and parity number. The overall least squares mean for service period and services per conception were 249±15.36 days and 1.99±0.13 numbers, respectively. The longest service period was 353 ±43.86 days in the year 1997 and the shortest service period was 151±27.70 days in the year 2006. When the data set was analyzed to examine the seasonal effect, the maximum least squares mean for service period (297±22.22) was observed days in winter season and minimum in spring season (216±33.01 days). Maximum calving (46.34%) were noted in humid hot season. Animals in first parity took longer period (316±13.58 days) for conception and short service period (221±57.80 days) was in animals having sixth parity number. Statistical analysis showed the highly significant effect of parity on service period (P<0.01). In case of services per conception, the maximum and minimum least squares mean were as 2.29±0.33 numbers in the year 1997 and 1.21±0.24 numbers in the year 2006, respectively. During the hot humid season, animals availed maximum services per conception (2.24±0.16) and minimum number 1.62±0.22 in spring season. Maximum services per conception (2.36±0.31) were recorded in animals when calved fifth time and minimum services per conception (1.69±0.51) after calving sixth time. Years of calving, seasons of calving and parity number had no significant effect on services per conception.
Keywords: Nili-Ravi Buffalo; service period; services per conception.